How the Disruption in Sexually Transmitted Infection Care Due to the COVID-19 Pandemic Could Lead to Increased Sexually Transmitted Infection Transmission Among Men Who Have Sex With Men in The Netherlands: A Mathematical Modeling Study. Issue 2 (10th February 2022) - Xiridou, Maria; Heijne, Janneke; Adam, Philippe; Op de Coul, Eline; Matser, Amy; de Wit, John; Wallinga, Jacco; van Benthem, Birgit
Abstract : A mathematical modeling study found that the disruption in sexually transmitted infection care due to COVID-19 might have resulted in a small increase in chlamydia prevalence, but a decrease in gonorrhea prevalence. Supplemental digital content is available in the text. Abstract : Background: During the COVID-19 pandemic, the disruption in care for sexually transmitted infections (STIs) and the social distancing measures have led to reductions in STI testing and sexual behavior. We assessed the impact of these COVID-19–related changes on transmission of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) among men who have sex with men (MSM) in The Netherlands. Methods: We developed a mathematical model for CT and NG transmission among MSM, accounting for COVID-19–related changes in sexual behavior and testing in 2020 to 2021. Changes in 2020 were estimated from data from the Dutch COVID-19, Sex, and Intimacy Survey among MSM and the National Database of STI Clinics. Because of the lack of data for 2021, we examined several scenarios covering a range of changes. Results: A reduction of 10% and 40% in STI testing of symptomatic and asymptomatic, respectively, individuals with a 10% to 20% reduction in numbers of casual partners (according to partner status and activity level) during the second lockdown, resulted in a 2.4% increase in CT prevalence, but a 2.8% decline in NG prevalence in 2021. A 5% and 30% reduction in STI testing of symptomatic and asymptomatic, respectively, individuals with the same reduction in casual partners resulted in a 0.6% increase in CT prevalence and a 4.9% decrease in NG prevalence in 2021. Conclusions: The disruption in STI care due to COVID-19 might have resulted in a small increase in CT prevalence, but a decrease in NG prevalence. Scaling up STI care is imperative to prevent increases in STI transmission.